Immunomodulatory Activity of Tyrosine Kinase Inhibitors to Elicit Cytotoxicity Against Cancer and Viral Infection - Climent, Núria; Plana, Montserrat (Frontiers in Pharmacology, 2019)
Tyrosine kinase inhibitors (TKIs) of aberrant tyrosine kinase (TK) activity have been widely used to treat chronic myeloid leukemia (CML) for decades in clinic. An area of growing interest is the reported ability of TKIs to induce immunomodulatory effects with anti-tumor and anti-viral activity, which appears to be mediated by directly or indirectly acting on immune cells. In selected cases of patients with CML, TKI treatment may be interrupted and a non-drug remission may be observed. In these patients, an immune mechanism of increased anti-tumor cytotoxic activity induced by chronic administration of TKIs has been suggested. TKIs increase some populations of Natural Killer (NK), NK-LGL, and T-LGLs cells especially in dasatinib treated CML patients infected with CMV. In addition, dasatinib increase responses against CMV and is able to inhibit HIV replication in vitro. Recent studies suggest that subclinical reactivation of CMV could drive expansion of specific subsets of NK, and T-cells with both anti-tumoral and anti-viral function. Therefore, the underlying mechanisms implicated in the expansion of this increased anti-tumor and anti-viral cytotoxic activity induced by TKIs could be a new therapeutic approach to take into account against cancer and viral infections such as HIV-1 infection. The present review will briefly summarize the immunomodulatory effects of TKIs on T cells, NKs and B cells. Therapeutic implications for modulating immunity against cancer and viral infections and critical open questions are also discussed.